2019
DOI: 10.1038/s41598-019-44549-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of TTF-1 Modulation of Cellular Sensitivity to Cisplatin

Abstract: The lung lineage master regulator gene, Thyroid Transcription Factor-1 (TTF-1, also known as NKX2-1), is used as a marker by pathologists to identify lung adenocarcinomas since TTF-1 is expressed in 60 ~ 70% of lung ADs. Much research has been conducted to investigate roles of TTF-1 in lung cancer biology. But, how it modulates cellular chemosensitivity remains poorly characterized. Our study shows that TTF-1 sensitizes the KRAS- mutated A549 and NCI-H460 lung cancer cells to cisplatin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…4,13 Despite its role as a "lineage-survival" oncogene in lung ADC, it has become apparent that TTF-1 expression is associated with a favorable prognosis in NSCLC, and some recent research found TTF-1 can modulate the sensitivity to cisplatin and connect with mutated EGFR, TTF-1 positive patients also display more favorable factors like actionable target mutation. [19][20][21][22] As more signaling partners of NKX2-1 are revealed, there will be opportunities to initiate translational research for creating and developing NKX2-1-dependent strategies as tools for managing NKX2-1-positive lung cancer. The limitations in our study might be the antibody used in the IHC test and that we retrospectively reviewed the patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,13 Despite its role as a "lineage-survival" oncogene in lung ADC, it has become apparent that TTF-1 expression is associated with a favorable prognosis in NSCLC, and some recent research found TTF-1 can modulate the sensitivity to cisplatin and connect with mutated EGFR, TTF-1 positive patients also display more favorable factors like actionable target mutation. [19][20][21][22] As more signaling partners of NKX2-1 are revealed, there will be opportunities to initiate translational research for creating and developing NKX2-1-dependent strategies as tools for managing NKX2-1-positive lung cancer. The limitations in our study might be the antibody used in the IHC test and that we retrospectively reviewed the patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that TTF-1 positive lung adenocarcinomas are dependent on the sustained expression of TTF-1 and that they sometimes exhibit focal copy number increases 4,13 . Despite its role as a “lineage-survival” oncogene in lung ADC, it has become apparent that TTF-1 expression is associated with a favorable prognosis in NSCLC, and some recent research found TTF-1 can modulate the sensitivity to cisplatin and connect with mutated EGFR, TTF-1 positive patients also display more favorable factors like actionable target mutation 19–22 . As more signaling partners of NKX2-1 are revealed, there will be opportunities to initiate translational research for creating and developing NKX2-1-dependent strategies as tools for managing NKX2-1–positive lung cancer.…”
Section: Discussionmentioning
confidence: 99%